2021
DOI: 10.3389/fenrg.2020.606494
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance All-Solid-State Lithium–Sulfur Batteries Enabled by Slurry-Coated Li6PS5Cl/S/C Composite Electrodes

Abstract: Among many lithium secondary batteries, lithium–sulfur batteries stand out because of their high theoretical specific energy, low cost, non-toxicity and the fact that they cause no environmental pollution. However, due to poor electronic and ionic conductivity, shuttle effect, lithium dendrites and other defects, it remains a big challenge to achieve large-scale application of lithium-sulfur batteries. Here we report an all-solid-state lithium–sulfur battery based on Li-argyrodite Li6PS5Cl solid-state electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…In addition, to determine the porosity of the LPSCl 1.5 – x NBR electrolyte films, the Archimedes drainage method was adopted . First, the obtained electrolyte films were soaked into a 1,3-dioxolane (DOL) solvent for 12 h since LPSCl 1.5 cannot dissolve in the DOL solution, as well as it does not react with the DOL solution . After that, the LPSCl 1.5 – x NBR electrolyte films were taken out from the DOL solvent and dried using a filter paper until no solvent dropped.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, to determine the porosity of the LPSCl 1.5 – x NBR electrolyte films, the Archimedes drainage method was adopted . First, the obtained electrolyte films were soaked into a 1,3-dioxolane (DOL) solvent for 12 h since LPSCl 1.5 cannot dissolve in the DOL solution, as well as it does not react with the DOL solution . After that, the LPSCl 1.5 – x NBR electrolyte films were taken out from the DOL solvent and dried using a filter paper until no solvent dropped.…”
Section: Methodsmentioning
confidence: 99%
“…31 First, the obtained electrolyte films were soaked into a 1,3-dioxolane (DOL) solvent for 12 h since LPSCl 1.5 cannot dissolve in the DOL solution, as well as it does not react with the DOL solution. 32 After that, the LPSCl 1.5 −xNBR electrolyte films were taken out from the DOL solvent and dried using a filter paper until no solvent dropped. The solvent uptake could be calculated by the mass difference of the electrolyte films before/after soaking in the DOL solvent.…”
Section: Preparation Of Lpscl 15 −Xnbr Electrolyte-integratedmentioning
confidence: 99%
“…28−30 be stable. Zheng et al 31 found that the Li 6 PS 5 Cl/S interface undergoes reductive degradation to form Li 3 P, LiP, Li 3 P 7 , or LiP 7 along with Li 2 S and LiCl. It also undergoes oxidative degradation, resulting in thiosulfate oligomerization, which releases polysulfides that lead to sluggish Li-ion transport and cathode overpotential.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The volatility of sulfur makes experimental characterization of these interfaces using traditional tools such as scanning electron microscopy and transmission electron microscopy challenging. Nevertheless, existing studies suggest that these interfaces might not be stable. Zheng et al . found that the Li 6 PS 5 Cl/S interface undergoes reductive degradation to form Li 3 P, LiP, Li 3 P 7 , or LiP 7 along with Li 2 S and LiCl.…”
Section: Introductionmentioning
confidence: 99%
“…et al, 2021;Pang et al, 2021). Therefore, significant research effort into LSB has potential advantages for future energy storage (Wang H. et al, 2017;Fan et al, 2021;Zheng et al, 2021;Phuc et al, 2022).…”
Section: Introductionmentioning
confidence: 99%